2020
DOI: 10.1016/j.jhepr.2020.100096
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for late-onset presentations of acute liver failure in Wilson's disease: The UK experience over 2 decades

Abstract: Background & Aims: Acute liver failure as the initial presentation of Wilson's disease is usually associated with onset in childhood, adolescence or early adulthood. Outcomes after transplantation for late-onset presentations, at or after 40 years, are seldom reported in the literature. Methods: We report a case, review the literature and provide unpublished data from the UK Transplant Registry on late-onset acute liver failure in Wilson's disease. Results: We describe the case of a 62-year-old man presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…In hepatic patients, a high rate of cirrhosis (77%) was reported at diagnosis, including 3 cases of fulminant decompensation with encephalopathy. The severity of liver damage at diagnosis should encourage physicians to screen widely for WD in the event of liver disease of unknown etiology, regardless of age, even in the case of severe presentation (eg, decompensated cirrhosis and acute liver failure) 10 . This is worthwhile because treatment is highly effective and hepatocellular carcinomas are not rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hepatic patients, a high rate of cirrhosis (77%) was reported at diagnosis, including 3 cases of fulminant decompensation with encephalopathy. The severity of liver damage at diagnosis should encourage physicians to screen widely for WD in the event of liver disease of unknown etiology, regardless of age, even in the case of severe presentation (eg, decompensated cirrhosis and acute liver failure) 10 . This is worthwhile because treatment is highly effective and hepatocellular carcinomas are not rare.…”
Section: Discussionmentioning
confidence: 99%
“…5 Late-onset WD forms diagnosed after age 40 years, or even after 70 years, are rarely reported; therefore, little is known about this phenotype. 6,7 To date, a few case reports [7][8][9][10][11][12][13][14] and a European study (n = 46), with limited data on neurological phenotyping, have described patients with late-onset WD. 15 In this current study, we analyzed a cohort of patients diagnosed after age 40 years, who were identified from the French Wilson's Disease Registry (FWDR).…”
mentioning
confidence: 99%
“…Late-onset presentation of WD as a cause of ALF is rare. There are few cases of first presentation of WD after the age of 40 years [ 15 ]. In the presented cohort, 1 woman was diagnosed at the age of 45 with K-F rings and was treated with a successful liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…But it is also important to make the diagnosis of WD prior to transplantation. Because organ transplant networks make special provision for acute liver failure (ALF) due to WD when considering the urgency of transplantation and the terminology relating to acute presentations of liver disease become relevant when listing a case of WD [11].…”
Section: Introductionmentioning
confidence: 99%